Facebook marketing for dummies - Dunay, Paul.; Krueger, Richard (Hoboken, N.J. : Wiley, 2011)
Recruit fans and turn them into customers! This book makes it easy to create a page, add applications to it, host an event, and much more. It's an easy-to-follow blueprint for marketing and promoting your organization on Facebook!
Previous ed.: 2010.
Includes index.
Keywords: Facebook (Electronic resource); Internet marketing; Internet advertising